COVID-19 pandemic impact on people with diabetes: results from a large representative sample of Italian older adults. Issue 5 (October 2022) - Vigezzi, Giacomo Pietro; Bertuccio, Paola; Bossi, Camilla Bonfadini; Amerio, Andrea; d'Oro, Luca Cavalieri; Derosa, Giuseppe; Iacoviello, Licia; Stuckler, David; Zucchi, Alberto; Lugo, Alessandra; Gallus, Silvano; Odone, Anna; et al.
Abstract: Aims: Restrictions imposed to prevent SARS-CoV-2 transmission should be weighed against consequences on vulnerable groups' health. Lifestyles and disease management of older people with diabetes might have been differentially impacted compared to non-chronic individuals. Methods: A cross-sectional study (LOST in Lombardia) was conducted on a representative full sample of 4 400 older adults (17 th -30 th November 2020), collecting data on lifestyles, mental health and access to care before and during the pandemic. Results: We compared 947 (51.9%) people with diabetes and 879 (48.1%) healthy subjects reporting no chronic conditions. People with diabetes reported more frequently increased physical activity (odds ratio, OR 2.65, 95% confidence internals, CI 1.69-4.13), drinks/week reduction (OR 6.27, 95%CI 3.59-10.95), increased consumption of fruit (OR 2.06, 95%CI 1.62-2.63), vegetables (OR 1.41, 95%CI 1.10-1.82), fish (OR 2.51, 95%CI 1.74-3.64) and olive oil (OR 3.54, 95%CI 2.30-5.46). People with diabetes increased telephone contacts with general practitioners (OR 3.70, 95%CI 2.83-4.83), hospitalisations (OR 9.01, 95%CI 3.96-20.51), visits and surgeries cancellations (OR 3.37, 95%CI 2.58-4.42) and treatment interruptions (OR 1.95, 95%CI 1.33-2.86). Conclusions: Pandemic adverse effects occurred but are heterogenous in a population with chronic diseases, who seized the opportunity to improve health behaviours, despite health system difficulties guaranteeing routine care, within and beyond COVID-19. Highlights: COVID-19 impacted disproportionally older people with diabetes compared to healthy subjects. People with diabetes were more likely to increase physical activity and reduce alcohol intake. Older people with diabetes shifted towards a more balanced diet. People with diabetes increased healthcare seeking in autumn 2020 compared to 2019. Pandemic proved to be an opportunity to design preventive interventions.